Children’s Perspectives on Robotics and the Relevance to Educational Robotics Competitions - Christoforou, Eftychios G.; Avgousti, Sotiris; Masouras, Panicos; Panayides, Andreas S. (My University, 2022)
Robotics is a challenging but also exciting scientific field which provides a framework for STEM (Science, Technology, Engineering, and Mathematics) education. An interview as part of a series of podcasts, called “Science Talks – Kids Edition”, produced by the University of Cyprus, allowed to identify the children’s perceptions and questions on robotics (elementary school and kindergarten ages).
Keywords: Robotics; Relevance; Educational Robotics Competitions; Perspectives; Children’s